Knowledge and Social Support as Determinants of Nurse Caring Behavior - Sujatmiko, Sujatmiko; Nursalam, Nursalam (Health Notions, 2017)
One of the nursing behavior is caring, which is an action that aims at giving physical care and noticing emotion while increasing either clientâs secure sense or safety. Good knowledge and good social support from the people are very needed by nurses in order to improve caring behavior to the patients. Moreover, this research aimed at knowing the correlation between either knowledge or social support and caring behavior of nurses at RSUD Nganjuk (regional hospital of Nganjuk). Design of this research was cross sectional. The population of this research was all of the nurses at RSUD Nganjuk who were 250 nurses (respondents). The samples were taken through purposive sampling and there were 100 respondents as the samples. The data was obtained through questionnaire and analyzed by Spearman Rank test with Î± = 0.05. The result of Spearman Rank test between the variable of knowledge and caring behavior showed  p-value = 0.000 (there was a significant correlation between nurseâs knowledge and caring behavior). The result of Spearman Rank test between social support and caring behavior showed p-value = 0.000 (there was a significant correlation between social support for nurses and caring behavior. Hospital training regarding caring needed to be given periodically for the nurses in order to support caring behavior. More effective caring behavior must begin to be given as early as possible in the institution of nursing education through lecture and practice/ novice.